2008
DOI: 10.1016/j.soildyn.2007.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Seismic hazard and risk in Shanghai and estimation of expected building damage

Abstract: The People's Republic of China is in the process of rapid demographic, economic and urban change including nationwide engineering and building construction at an unprecedented scale. The mega-city of Shanghai is at the centre of China's modernisation. Rapid urbanisation and building growth have increased the exposure of people and property to natural disasters. The seismic hazard of Shanghai and its vicinity is presented from a seismogenic free-zone methodology. A PGA value of 49 cm s À2 and a maximum intensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Rashed and Weeks, 2003;Maithani and Sokhi, 2004;Servi, 2004;Gulati, 2006;Thapaliya, 2006;Cole et al, 2008;Nath and Thingbaijam, 2009). Therefore, many Iranian researchers such as Zahraie and Ershad (2005), Aghataher et al (2008), Amini Hosseini et al (2009), Hataminejad et al (2009) and Hashemi and Alesheikh (2012) have identified the effective factors in earthquake hazard assessment and applied various methods in developing a seismic hazard map.…”
Section: Introductionmentioning
confidence: 99%
“…Rashed and Weeks, 2003;Maithani and Sokhi, 2004;Servi, 2004;Gulati, 2006;Thapaliya, 2006;Cole et al, 2008;Nath and Thingbaijam, 2009). Therefore, many Iranian researchers such as Zahraie and Ershad (2005), Aghataher et al (2008), Amini Hosseini et al (2009), Hataminejad et al (2009) and Hashemi and Alesheikh (2012) have identified the effective factors in earthquake hazard assessment and applied various methods in developing a seismic hazard map.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, vulnerability assessment and modelling behaviour of buildings related to earthquakes are a major concept in hazards studies [2,8,19,[27][28][29][30][31][32][33][34][35]. These investigations have identified the effective factors in earthquake hazard assessment and applied different methods for producing a seismic hazard map.…”
Section: Introductionmentioning
confidence: 99%
“…Various other analytical methods, such as probabilistic analysis [21,22] and Monte Carlo simulation [23][24][25], have also been used to evaluate building damage caused by natural disasters [26]. In recent years, research has used artificial intelligence such as data mining and machine learning to identify and evaluate natural disaster risk factors.…”
Section: Introductionmentioning
confidence: 99%